Studi Nuzulul Qur’an dalam Kajian Al-Qur’an Surat Al-Baqarah Ayat 185 - Anshory, Muhammad Isa; Aziz, Nur; Al Faizi, Ahmad Akbar; Dewi, Rachma Rusdiana (Lembaga Yasin AlSys, 2025)
This research aims to analyze the concept of Nuzulul Qur'an in the context of Al-Baqarah verse 185, which concerns the obligation to fast in the month of Ramadan. Nuzulul Qur'an refers to the gradual decline of Allah's revelations to the Prophet Muhammad SAW over 23 years. Surah Al-Baqarah verse 185 explains the rules for implementing fasting during the month of Ramadan, as well as the wisdom behind this obligation. This research uses a historical interpretation approach (tafsir asbabun nuzul) to explore the background to the revelation of this verse and its relevance in the social and religious context of that time. Apart from that, this research also examines the application of this verse in the lives of Muslims from a theological and practical perspective. The research results show that this verse was revealed as a response to the situation of the people of Mecca who at that time needed practical guidance regarding fasting. This research also highlights the deep meaning behind fasting as a means of spiritual formation, building self-discipline, and increasing social awareness. Thus, it is hoped that this research can provide a more comprehensive understanding of the importance of the values ​​contained in this verse and their relevance in the lives of Muslims today.